Navigational cue effects in Alzheimer's disease and posterior cortical atrophy. Issue 6 (20th April 2018) - Yong, Keir X. X.; McCarthy, Ian D.; Poole, Teresa; Suzuki, Tatsuto; Yang, Biao; Carton, Amelia M.; Holloway, Catherine; Papadosifos, Nikolaos; Boampong, Derrick; Langham, Julia; Slattery, Catherine F.; Paterson, Ross W.; et al.
Abstract: Objective: Deficits in spatial navigation are characteristic and disabling features of typical Alzheimer's disease (tAD) and posterior cortical atrophy (PCA). Visual cues have been proposed to mitigate such deficits; however, there is currently little empirical evidence for their use. Methods: The effect of visual cues on visually guided navigation was assessed within a simplified real‐world setting in individuals with tAD ( n  = 10), PCA ( n  = 8), and healthy controls ( n  = 12). In a repeated‐measures design comprising 36 trials, participants walked to a visible target destination (an open door within a built environment), with or without the presence of an obstacle. Contrast and motion‐based cues were evaluated; both aimed to facilitate performance by applying perceptual changes to target destinations without carrying explicit information. The primary outcome was completion time; secondary outcomes were measures of fixation position and walking path directness during consecutive task phases, determined using mobile eyetracking and motion capture methods. Results: Results illustrate marked deficits in patients' navigational ability, with patient groups taking an estimated two to three times longer to reach target destinations than controls and exhibiting tortuous walking paths. There were no significant differences between tAD and PCA task performance. Overall, patients took less time to reach target destinations under cue conditions (contrast‐cue: 11.8%; 95% CI: [2.5, 20.3]) and were more likely initially to fixate on targets. Interpretation: The study evaluated navigation to destinations within a real‐world environment. There is evidence that introducing perceptual changes to the environment may improve patients' navigational ability.